The Central Utah Project on Individualization of Instruction - Brimley, Vern.; Provo City School District, UT. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
This report describes and evaluates in narrative form methods of individualizing instruction utilizing published and/or devised programmed materials. The Needs Inventory Program, Learning Disabilities Workshop, Family Education Program, and specific grade-level programs are described. A teacher survey showed a favorable response to these programs. Complete evaluative data on each area of the project is appended. (NS)
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Contract Number: OEG-6-4-7-67825-6123.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Diagnosis; Individual Instruction; Individualized Programs; Program Evaluation; Teacher Attitudes